Diagnostic and prognostic value of serum NfL and p-Tau181 in frontotemporal lobar degeneration. Issue 9 (1st July 2020) - Benussi, Alberto; Karikari, Thomas K; Ashton, Nicholas; Gazzina, Stefano; Premi, Enrico; Benussi, Luisa; Ghidoni, Roberta; Rodriguez, Juan Lantero; Emeršič, Andreja; Simrén, Joel; Binetti, Giuliano; Fostinelli, Silvia; et al.
Abstract : Objective: To assess the diagnostic and prognostic value of serum neurofilament light (NfL) and serum phospho-Tau181 (p-Tau181 ) in a large cohort of patients with frontotemporal lobar degeneration (FTLD). Methods: In this retrospective study, performed on 417 participants, we analysed serum NfL and p-Tau181 concentrations with an ultrasensitive single molecule array (Simoa) approach. We assessed the diagnostic values of serum biomarkers in the differential diagnosis between FTLD, Alzheimer's disease (AD) and healthy ageing; their role as markers of disease severity assessing the correlation with clinical variables, cross-sectional brain imaging and neurophysiological data; their role as prognostic markers, considering their ability to predict survival probability in FTLD. Results: We observed significantly higher levels of serum NfL in patients with FTLD syndromes, compared with healthy controls, and lower levels of p-Tau181 compared with patients with AD. Serum NfL concentrations showed a high accuracy in discriminating between FTLD and healthy controls (area under the curve (AUC): 0.86, p<0.001), while serum p-Tau181 showed high accuracy in differentiating FTLD from patients with AD (AUC: 0.93, p<0.001). In FTLD, serum NfL levels correlated with measures of cognitive function, disease severity and behavioural disturbances and were associated with frontotemporal atrophy and indirect measures of GABAergic deficit. Moreover, serum NfL concentrations were identified as the best predictors of survival probability. Conclusions: The assessment of serum NfL and p-Tau181 may provide a comprehensive view of FTLD, aiding in the differential diagnosis, in staging disease severity and in defining survival probability.